Use of coconut milk versus dairy milk in malaysian cuisines : comparison of nutritional value - Shaharuddin, Nurulazizah (Universiti Sains Malaysia, 2013)
Most of the food in our Malaysian cuisine uses coconut milk in their cooking including main dishes and desserts. But, the use of dairy milk as substitute of coconut milk in cooking is very less used by the community. Today, our community has less exposure on coconut milk and dairy milk as well as their different uses. Lately, there has been suggestion to use dairy milk as a healthier alternative to use in everyday cooking as a replacement for coconut milk which is believed to be unhealthy. This study was conducted to determine the nutritional values and sensory evaluation of Malaysian cuisines prepared with coconut and dairy milk. Custard pudding and ‘gulai lemak cili padi’ were cooked using fresh coconut milk (FCM), instant coconut milk (ICM), fresh milk (FM) and evaporated milk (EM). Proximate analysis was carried out following the procedures of AOAC (1996). Sensory evaluation was carried out using 7 point hedonic scale to determine the consumer is acceptability of the products. Data obtained was analyzed using SPSS 20.0 software. The results showed that custard pudding prepared using FM had a significantly (P < 0.05) lowest calorie content (3.855 kcal/g) compared with custard pudding prepared with FCM (4.690 kcal/g), ICM (4.679 kcal/g) and FM (4.178 kcal/g). The fat content (0.28%) in FM custard pudding was also significantly lowest (P < 0.05) while FCM showed the highest (11.61 %) followed by ICM (8.50%) and EM (2.75 %). The highest protein content was found in EM custard pudding (2.98%). The ‘gulai lemak cili padi’ showed similar results, with FM ‘gulai lemak cili padi’ by having significantly (P < 0.05) lowest calorie (4.681 kcal/g) and fat content (5.68%) among others. The highest content of calorie was (6.764 kcal/g) and fat (57.46 %) were showed by ICM among others. Whereas, the highest protein content was found in FM (5.53%) and the lowest was showed in ICM (0.37%). The sensory evaluation results showed that custard pudding prepared with FCM was the most appealing compared with others as it received significantly highest scores (P < 0.05) in all sensory attributes namely aroma (6.06), colour (6.06), appearance (5.60), creaminess (5.30), firmness (5.20), flavor (5.84) and overall acceptance (5.96). Similarly, the ‘gulai lemak cili padi’ prepared using FCM had significantly the highest acceptability (P 0.05) score in terms of aroma (5.22), colour (5.68), flavor (5.20) and overall acceptability (5.48). Panelists equally accepted ‘gulai lemak cili padi’ made with FCM and ICM as regards to creaminess and oiliness attributes. In conclusion, more work should be done to improve the acceptability of Malaysian cuisines made with dairy milk as consumers are not willing to sacrifice the classic flavour of coconut milk they have used to.